THE ADVENTURE OF WALKING THE CAMINO DE SANTIAGO TRAILS FROM THE PERSPECTIVE OF DUVINGNAUD (Fiep Bulletin - online, 2015)
In his search to occupy his free time, man reencounters the ludic element of life through leisure activity which had distanced itself long ago and reappears in new clothes. Presently, people migrate from the city to the country and explore trails and paths, searching for ludic, aesthetic and instinctive emotions. This spirit of adventure can also be associated with the ludic world, a very ample field which few people dare to explore. Duvignaud (1997) shows the importance of us recognizing the ludic world that invades all collective, human existence, beginning with daydreaming, dreaming or staging, conviviality, festivity and reaching the innumerous facets of our imaginary world. The motivation to discover the meanings that the trekking adventure acquires, in the fantasy world of pilgrim-hikers that walk the Caminho do Sol (Path of the Sun), emerged from Duvignaud's perspective. The trekkers' depositions revealed their need to get away from day-to-day habits and to contemplate themselves, having nature as a facilitating element. This escaping from the routine seems to be the ludic outlet that Duvignaud mentions from Sartre. This moment was identified in the walkers' discourses where they show themselves to be far from the real world, distanced from everyday rules, launching themselves into new games, thoughts, desires and needs. Feelings like solidarity, self-knowledge, surpassing and transcendence bloom. Set in motion by the harmony between pleasure and imagination, these individuals, nature's pilgrim-walkers, unleash the ludic process within themselves. Leisure time and nature's space were facilitators of this process and of the growth of the human spirit of these hikers. Walking in nature is reencountering oneself, one's own nature, and not just practicing trekking, but entering the ludic space which exists within us.